Physical Activity in adults and elderly adults measured by accelerometry - The influences of age group, gender, time of year, and weather - Bento, Teresa (2011)
Physical activity in adults and elderly adults measured by accelerometry: the influences of age group, gender, time of year, and weather. Abstract The main purpose of this thesis was to study objectively measured physical activity (PA) in an adult Portuguese population. Specifically, we aimed to a) address methodological concerns related to the assessment of PA by means of accelerometry; b) provide descriptive data on PA, including the analysis of gender/age differences with regard to PA and investigation of the fulfilment of PA recommendations; c) examine if there are changes in PA when assessed at different times of the year; and d) explore the effects of weather on PA. Data indicate that intervention strategies should focus on ensuring the maintenance of a consistent PA level throughout the year by encouraging the accomplishment of daily goals based on the number of steps taken per day, which should be adjusted according to the gender/age characteristics of the targeted population. Intervention strategies should also emphasise the importance of compliance with PA recommendations to the general population, but especially to the elderly. Moreover, surveillance data based on accurate criteria should be considered to measure the achievement of the intervention objectives. The results of this study contribute to the knowledge of the PA of the Portuguese population and will facilitate the improvement of PA promotion strategies and intervention programmes. This study also provides recommendations that could help to potentiate interventions that are aimed at increasing daily PA levels and inverting sedentary behaviours throughout the year and across age groups. Key words: accelerometry, elderly, physical activity, recommendations, steps, surveillance, weather Actividade física em adultos e idosos avaliados por acelerometria – influência do grupo etário, género, período do ano e do clima Abstract O principal objectivo desta tese foi estudar a actividade física (AF) de adultos e idosos portugueses quando avaliada por acelerometria. Mais especificamente pretendemos a) estudar questões metodológicas relacionadas com a avaliação da AF através de acelerometria; b) fornecer dados descritivos da AF avaliada objectivamente, incluindo as análise das diferenças entre géneros e níveis etários, e do cumprimento das recomendações da AF; c) examinar as alterações na AF, quando avaliada em várias alturas do ano; e d) explorar os efeitos do clima no envolvimento na AF. Os resultados obtidos indicam que as campanhas de promoção da AF devem focar-se no aumento dos níveis de participação na AF, assim como garantir a sua manutenção ao longo do ano. As estratégias de intervenção devem passar pelo cumprimento de objectivos diários baseados no número de passos, e ser enfatizado o cumprimento de períodos de pelo menos 10 minutos de intensidade moderada a vigorosa no cumprimento dos 30 minutos diários acumulados de AF na população em geral, mas em especial nos idosos. Finalmente, deve promover-se a padronização de procedimentos e a recolha de dados sistemáticos que permitam reportar as alterações verificadas nas características da população no cumprimento destes objectivos. Os resultados deste estudo contribuem para o conhecimento dos níveis de AF da população portuguesa, do seu desempenho no cumprimento das recomendações de AF, das alterações que verificam ao longo do ano, e dos factores que podem afectar o seu envolvimento na AF. Estes dados são também contributos para a melhor adequação das estratégias de promoção e dos programas de intervenção de AF já que constituem pistas acerca de como potenciar intervenções que tenham como objectivo aumentar os níveis diários de AF e inverter os hábitos sedentários, quer ao longo do ano, quer da idade. Key words: acelerometria, idosos, actividade física, recomendações, passos, vigilância, clima